Writings on May 13. - Funston, Neil John (Universiti Kebangsaan Malaysia, 1975)
The racial riots which started in Kuala Lumpur on the evening of May, 13, 1969, or the May 13 Incident as it has since come to be known, is one of the most controversial political events in Malaysia's history. The following article is not another account of this event, but an analysis of the writings spawned by it. It has the threefold task of: presenting a descriptive inventory of the various interpretations of why it occurred and the implications it holds for the country's future; analyzing these writings as an example of the development of political science in relation to Malaysia generally; and examining the manner in which these writings will themselves affect future perceptions of Malaysian politics. The major conclusions are that the accounts under review, by adhering to the conventional wisdom on the functioning of the Malaysian political system, work within a theoretical frame work that is gravely inadequate, and that they fail to substantiate the general preoccupation with the dangers of post-May 13 Malay nationalism.